Handwashing promotion impact on the incidence of diarrhoea durng pandemic times due to respiratory viruses in Costa Rica - Mora-Alvarado, Darner A. (2022)
The present study analysesed the impact of hygiene and handwashing with potable drinking water and soap on the incidence of acute diarrhoea diseases (ADD) during pandemic times due to respiratory viruses AH1N1 (2009) and SARS-CoV-2 (2019). In this appraisal, we have reviewed the incidence rate of diarrhoea per 100 000 population from 2017 to 2020. Additionally, we have identified the strategies of the handwashing and hygiene promotion during the pandemics, and we have gathered data on drinking water coverage. Results showed that promoting hygiene and handwashing with drinking water and soap has reduced the incidence rate of ADD/100 000 population during 2009 and 2020 reaching 56% of reduction during the sanitary crisis cause by COVID-19. Even though an extensive drinking water coverage throughout the country is crucial for proper handwashing, educating people is needed to significantly reduce the incidence rate of diarrhoea. In conclusion, promoting hygiene and handwashing persistently is fundamental to minimise respiratory and enteric diseases.